Porous Cellulose Beads Fabricated from Regenerated Cellulose as Potential Drug Delivery Carriers - Lee Ken Voon; Suh Cem Pang; Suk Fun Chin (Journal of Chemistry)
Highly porous cellulose beads (CBs) of various mean sizes were successfully prepared from regenerated cellulose of paper wastes. The drug delivery characteristics of CBs with different mean sizes were investigated using curcumin as the model drug under controlled conditions. The loading capacity and efficiency of curcumin onto CBs were substantially influenced by factors such as their morphological characteristics, curcumin concentration, and duration of loading. The release kinetic profiles of curcumin from CBs of different mean sizes were investigated in media of pH values resembling digestive juices and intestinal fluids. Release kinetic models were used to simulate and elucidate release kinetics and mechanisms of curcumin from CBs under specific conditions. The loading capacity and efficiency of curcumin onto CBs could be enhanced via the optimization of curcumin solution concentration and the morphological characteristics of CBs, whereas the release kinetic profiles of curcumin from CBs could be modulated by varying the mean diameter of CBs. Optimized CBs derived from regenerated cellulose of paper wastes are potentially useful as cost-effective drug delivery carriers.